Analisis Tingkat Ketergantungan Fiskal dan Hubungannya dengan Pertumbuhan Ekonomi Kota Jambi - Dito Wijaya; Haryadi Haryadi; Zulgani Zulgani (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2015)
This study aimed to quantify the fiscal needs in the city jambi and analyze the relationship between the level of fiscal dependency of between the level of fiscal dependency of economic growth in the city of Jambi and see how big the city’s fiscal dependence on the central govermeny Jambi. The results of this study indicate that the Fiscal Needs in Jambi has increased significantly each year, with an average growth of 27 times greater where the level of dependence of the Local Government Fiscal Jambi city against the central government is still very High, on average within 6 year (2008 to 2013) obtained the proportion of revenue to the level of fiscal decentralization Jambi each including a small category with an average of 10.93%. This suggests that the fiscal capacity of the city of Jambi to implement regional autonomy means that the dependency ratio is the small city of Jambi to the central government is very high at 89.07 to the relationship between the Fiscal Dependence Levels of Economic Growth in Jambi indicates perfect correlation and positive direction.